Knowledge on dehydration during physical activity among physical education teachers in jaffna district - Mathana, S.; Jeganenthirana, S. (University of Jaffna, 2018)
In recent years, dehydration issues are increasing dramatically in Jaffna district. An awareness level of physical education teachers on preventing dehydration is considered as one of the main factor. Major objective of this study is to assess the level of knowledge on dehydration during physical activity among physical education teachers in Jaffna district. One hundred and twenty three physical education teachers were randomly selected as subjects from 180 teachers. The data were collected by self-administrated questionnaire. Collected data were statistically analyzed by descriptive statistic technique. The results revealed that the knowledge level of the teachers in Jaffna district was 33.292 out of 100. Study revealed that physical education teachers’ level of knowledge on preventing dehydration issues in Jaffna district was poor. Hence, effective dehydration education will support to enhance knowledge level of physical education teachers on preventing dehydration issues in Jaffna district was recommended.
Keywords: Dehydration; Knowledge; Physical; Prevention